Day 2 - 1620 - Yang.pdf - Gill, Philip (Cranfield University, 2023)
EVALUATION OF NITROCELLULOSE AND GUN PROPELLANTS MADE WITH KRAFT CELLULOSE Dr. Kathy Yang - US Army 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'